Chemical Composition Analysis, Cytotoxic, Antimicrobial and Antioxidant Activities of Physalis angulata L.: A Comparative Study of Leaves and Fruit - Jayachithra Ramakrishna Pillai; Adil Farooq Wali; Godfred Antony Menezes; Muneeb U. Rehman; Tanveer A. Wani; Azher Arafah; Seema Zargar; Tahir Maqbool Mir (Molecules, 2022)
Physalis angulata L. belongs to the family Solanaceae and is distributed throughout the tropical and subtropical regions. Physalis angulata leaf and fruit extracts were assessed for in vitro anticancer, antioxidant activity, and total phenolic and flavonoid content. The GC-MS technique investigated the chemical composition and structure of bioactive chemicals reported in extracts. The anticancer activity results revealed a decrease in the percentage of anticancer cells’ viability in a concentration- and time-dependent way. We also noticed morphological alterations in the cells, which we believe are related to Physalis angulata extracts. Under light microscopy, we observed that as the concentration of ethanolic extract (fruit and leaves) treated HeLa cells increased, the number of cells began to decrease.